Spectrum of germline and somatic mitochondrial DNA variants in Tuberous Sclerosis Complex - Giannikou, Krinio; Martin, Katie R.; Abdel-Azim, Ahmad G.; Pamir, Kaila J.; Hougard, Thomas R.; Bagwe, Shefali; Tang, Yan; MacKeigan, Jeffrey P.; Kwiatkowski, David J.; Henske, Elizabeth P.; Lam, Hilaire C. (Frontiers in Genetics, 2023)
Tuberous Sclerosis Complex (TSC) is caused by loss of function variants in either TSC1 or TSC2 and is characterized by broad phenotypic heterogeneity. Currently, there is limited knowledge regarding the role of the mitochondrial genome (mtDNA) in TSC pathogenesis. In this study, we aimed to determine the prevalence and spectrum of germline and somatic mtDNA variants in TSC and identify potential disease modifiers. Analysis of mtDNA amplicon massively parallel sequencing (aMPS) data, off-target mtDNA from whole-exome sequencing (WES), and qPCR, revealed mtDNA alterations in 270 diverse tissues (139 TSC-associated tumors and 131 normal tissue samples) from 199 patients and six healthy individuals. Correlation of clinical features to mtDNA variants and haplogroup analysis was done in 102 buccal swabs (age: 20-71). No correlation was found between clinical features and either mtDNA variants or haplogroups. There were no pathogenic variants in the buccal swab samples. Using in silico analysis, we identified three predicted pathogenic variants in tumor samples: MT-ND4 (m.11742G>A, p.Cys328Tyr, VAF: 43%, kidney angiomyolipoma), MT-CYB (m.14775T>C, p.Leu10Pro, VAF: 43%, LAM abdominal tumor) and MT-CYB (m.15555C>T, p.Pro270Leu, VAF: 7%, renal cell carcinoma). Large deletions of the mitochondrial genome were not detected. Analysis of tumors from 23 patients with corresponding normal tissue did not reveal any recurrent tumor-associated somatic variants. The mtDNA/gDNA ratio between tumors and corresponding normal tissue was also unchanged. Overall, our findings demonstrate that the mitochondrial genome is highly stable across tissues and within TSC-associated tumors.